ANALISIS PENGARUH NILAI TUKAR, SUKU BUNGA DAN INFLASI TERHADAP HARGA SAHAM PADA PT BANK CENTRAL ASIA Tbk TAHUN 2012-2016 - -, Maya Widiastuti (EKONOMIA, 2019)
This research is conducted on the basis of the movement of capital markets that are influenced by macro fudamental factors namely exchange rate, interest rate and inflation as things investors need to know before making long-term investment decisions. The state of the economy and the ups and downs of macro variables within a country can affect stock prices. Stock price fluctuations influenced by external factors or often referred to as market risk (macro fudamental) have properties that can not be controlled company.There are several findings in this study. First exchange rate has a positive and significant effect partially to stock price, hence can be said that hypothesis accepted. Secondly, interest rates have a positive and significant effect on stock prices, in this finding the hypothesis is rejected. The third inflation has a negative and insignificant effect on the stock price of PT Bank Central Asia Tbk, then the hypothesis is accepted. The four exchange rates, interest rates and inflation simultaneously have a significant effect on stock prices, these findings suggest that the hypothesis is accepted.